2010
DOI: 10.1051/0004-6361/201015146
|View full text |Cite
|
Sign up to set email alerts
|

Photospheric flux cancellation and associated flux rope formation and eruption

Abstract: Aims. We study an evolving bipolar active region that exhibits flux cancellation at the internal polarity inversion line, the formation of a soft X-ray sigmoid along the inversion line and a coronal mass ejection. The aim is to investigate the quantity of flux cancellation that is involved in flux rope formation in the time period leading up to the eruption. Methods. The active region is studied using its extreme ultraviolet and soft X-ray emissions as it evolves from a sheared arcade to flux rope configuratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
241
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(267 citation statements)
references
References 51 publications
15
241
7
Order By: Relevance
“…The limiting axial flux given in Savcheva and van Ballegooijen (2009) for a fourth, strongly decayed and sigmoidal active region, compares with the amount of unsigned flux in the region to a limiting ratio of roughly 14%. This contrasts sharply with Green et al (2011), who showed, using an observational study, that a flux rope formed by flux cancellation may contain as much as 60% of the unsigned flux of the active region. Savcheva et al (2012) carried out a study to try and reconcile the above discrepancy between the observational value of flux rope flux content and that found for a modelled flux rope.…”
Section: Modelling Magnetic Flux Ropes In the Decay Phasecontrasting
confidence: 71%
See 3 more Smart Citations
“…The limiting axial flux given in Savcheva and van Ballegooijen (2009) for a fourth, strongly decayed and sigmoidal active region, compares with the amount of unsigned flux in the region to a limiting ratio of roughly 14%. This contrasts sharply with Green et al (2011), who showed, using an observational study, that a flux rope formed by flux cancellation may contain as much as 60% of the unsigned flux of the active region. Savcheva et al (2012) carried out a study to try and reconcile the above discrepancy between the observational value of flux rope flux content and that found for a modelled flux rope.…”
Section: Modelling Magnetic Flux Ropes In the Decay Phasecontrasting
confidence: 71%
“…The results for four flux ropes for which it was possible to compare the rope's axial flux to the unsigned flux of the active region just before the eruption showed the ratios 18%, 16%, 58% and 50%. The region studied in Green et al (2011) was also modelled and there was an excellent agreement in the value found between these two approaches.…”
Section: Modelling Magnetic Flux Ropes In the Decay Phasementioning
confidence: 65%
See 2 more Smart Citations
“…The local correlation tracking (LCT) method is mainly applied to magnetic field polarities to explain eruptions or flares with MDI data (1.96 arcsec pixel size) and only recently with HMI data (0.5 arcsec pixel size). The aim of these analyses mainly concerns the onsets of the eruptions or flares (Ahn et al 2010;Zhou et al 2006;Green et al 2011;Liu et al 2012). The LCT method has also been applied to tracking granules.…”
Section: Introductionmentioning
confidence: 99%